Aktivitas Antifungi Ekstrak Akar Mahoni terhadap Isolat Botryodiplodia theobromae Pat. Penyebab Mati Pucuk pada Bibit Jabon (Antifungal Activity of Mahogany Root Extracts against Botryodiplodia theobromae Pat. Isolate Causing Dieback on Jabon Seedling) - Syamsul Falah; Achmad Achmad; Aji Winara (Masyarakat Peneliti Kayu Indonesia, 2015)
Dieback on jabon (Anthocephalus cadamba (Roxb.) Miq.) seedling caused by fungi Botryodiplodia theobromae Pat. decreased seedling’s quality and nurseries economic benefits. The control of dieback pathogen on jabon seedling used biofungicide from plant extract have not been studied intensively nowadays. Mahogany (Swietenia macrophylla King.) is one of the promising medicinal plants in Indonesia but its utilization as a biofungicide specially for controlling the dieback on jabon seedling has not been reported. This research aimed to examine the antifungal activities of mahogany root extracts against B.theobromae isolate causing dieback on jabon seedling in vitro. The poisoned food technique was used in assay of the antifungal activities of mahogany root extract. The result showed that mahogany root extract has antifungal activities against B.theobromae with the highest efective growth inhibition was the metanol solvent on 50% concentration level. Microscopical examination showed the inhibition of mycelium growth was caused by the changes on hyphae morphology and growth direction which were beads formation and curling.Keywords: antifungal, Botryodiplodia theobromae, jabon, mahogany root